2005
DOI: 10.1007/s10198-004-0254-1
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of human papillomavirus screening for cervical cancer

Abstract: We compared findings from recent studies modelling the cost-effectiveness of screening for cervical cancer using human papillomavirus (HPV) testing and alternative strategies. Data were standardized to facilitate comparison of costs per life year or costs per QALY gained in six studies. Absolute changes in costs, life years and QALYs for each strategy were normalized to a comparison with no screening. Costs were standardized to US$ in 2000 values. Most models assume screening starts at age 18 or 20 years. Assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 15 publications
4
44
0
3
Order By: Relevance
“…Only the group of probes designed to detect high-risk HPV types 16,18,31,33,35,39,45, 51, 52, 56, 59 and 68 was used. HC2 results were expressed as the ratio of the specimen's light emission to that of three concurrently tested 1 pg/mL HPV-DNA controls (relative light units [RLU]).…”
Section: Molecular and Cytological Procedures And Quality Controlsmentioning
confidence: 99%
“…Only the group of probes designed to detect high-risk HPV types 16,18,31,33,35,39,45, 51, 52, 56, 59 and 68 was used. HC2 results were expressed as the ratio of the specimen's light emission to that of three concurrently tested 1 pg/mL HPV-DNA controls (relative light units [RLU]).…”
Section: Molecular and Cytological Procedures And Quality Controlsmentioning
confidence: 99%
“…In the literature, the majority of studies on the cost of cervical cancer only consider screening (Zappa et al, 1998;Holmes et al, 2005). The costs of care for cervical cancer are often approached with overall estimates of the utilized resources (Schaffer et al, 1994) or models based on treatment protocols that may be different from clinical practices (Fahs et al, 1992;Rocconi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…46 By contrast, studies using liquid based cytology and HPV DNA testing have reported costs from 121 USD to 184,000 USD per life year saved or per quality-adjusted life-year (QALY). [11][12][13][14][15][16][17][18][19][20][21][22] Possible reasons for discrepancies include the fact that we did not include screening of young women in our model, the setting with organized screening, the setting with midwives (who have lower salaries than doctors) for taking smears, population-based real-life input data and analysis using a probabilistic state transition model.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Several studies have evaluated the economic impact of cervical screening with and without HPV testing, but have reported variable results. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Possible reasons for discrepancies include different modeling methodologies, use of surrogate endpoints and use of input data based on clinical studies that may not have been representative of the population as a whole. However, most modeling studies have consistently found similar reductions of the cumulative lifetime risk of invasive cervical cancer as a result of cytology and HPV DNA screening.…”
mentioning
confidence: 99%
See 1 more Smart Citation